Testing Women With Endometrial Cancer for Lynch Syndrome: Should We Test All? - Ma, Jun (Harborside Press, 2013)
Women with Lynch syndrome (LS) are at equal or higher risk for gynecologic cancers compared with their risk for colorectal cancer (CRC). Endometrial cancer (EC) often precedes CRC as patients’ sentinel malignancy. Identifying these patients is believed to reduce their substantial risk for synchronous and metachronous tumors and has profound implications for reducing cancer-related morbidity and mortality in other family members. Routine screening of patients with CRC for LS has become increasingly common, but routine screening for LS in women with EC is rarely performed. Current screening guidelines for identifying LS in women with EC vary but rely heavily on patient age and personal/family history, with or without incorporation of tumor pathology. Because each of these strategies misses a significant proportion of women with LS, more inclusive screening strategies that make good economic and clinical sense are needed. In recent years, emerging medicoeconomic evidence supports the fact that screening EC patients for LS may be cost-effective. Implementation of such a strategy requires multidisciplinary collaboration and partnership.